Biomaterial and Mesenchymal Stem Cell for Articular Cartilage Reconstruction - Shen, Yun; Fu, Yao; Wang, Jing; Li, Guo; Zhang, Xu; Xu, Yuanzhi; Lin, Yunfeng (Current Stem Cell Research & Therapy, 2014)
Cartilage has poor ability of spontaneous repair. Traditional treatments such as microfracture, bone drilling and autologous osteochondral graft were not fully satisfactory to fulfill the clinical needs. The idea of mesenchymal stem cell (MSCs-based cartilage regeneration has been put forward for decades. Large number of studies have been conducted on the biological properties of MSCs, the factors which might facilitate chondrogenic differentiation of MSCs, as well as the scaffold materials for tissue engineering. Promising results have been reported for cartilage repair in animal models. But before massive clinical application of MSCs, more efforts are needed on: differentiation improvement toward mature cartilage chondrocytes instead of hypertrophic chondrocyes and in vitro/in vivo phenotype maintenance; engineering an ideal biomaterial, which can meet the needs of the cartilage regeneration; and performing more studies on critical defects of large animals.
Keywords: chondrogenic differentiation